Escola, igualdade e diferenças - Machado, Joaquim (2013)
The Portuguese school claims to support a holistic approach to human beings development and is presented as a school for everyone, but it is organized according to principles of uniformity and impersonality ignoring individual characteristics. It claims to ensure universal teaching and to implement curriculum flexibility and pedagogical differences, but the main focus is on curriculum with predefined subjects, inflexible timetables and fixed classrooms. The emphasis on a concept of Education for All brings into question the school about the way it deals with differences, which draws the attention for the contradiction of exclusion through inclusion itself, demanding the restructuring of school and the changing of the school system administration’s processes.